PENGARUH PERMAINAN PLUMBERS SMART TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK NURUL IMAN KOTA PEKANBARU - Gatri Yolanda; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this research is to know the effect of the plumbers smart ability to recognize number concept of children aged 5-6 years. The research is conducted in TK Nurul Iman Pekanbaru City from April to Mey 2018. This is pretest and posttest group design an experimental research with 30 children as samples. Type of instument used in this study is the observation using a sheet to record about activities that occured during a given treatment. Based on the hypothesis test results obtained are the game plumbers smart is effect ability to recognize the number concept to children aged 55-6 years in TK Nurul Iman Pekanbaru City. Retrieved tcount at 4,688 with sig 0,000, because sig <0.05 then we can conclude that are effect of the ability to recognize the number concept is significant between class with plumbers smart game and without plumbers smart game. Hypothesis testing can be seen at tcount=4,688> t table=2,048 it has been suggested that there is significant effect in results between the control class and experiment class. The plumbers smart had a significant effect toward children age 5-6 years old ability to recognize the number concept, at 56,18% this is know from the different results ability to recognize the number concept on control class and experiment class with given the plumbers smart game treatment.Keywords: The Ability To Recognie The Number Concept, Plumbers Smart